Identifying the impediments and enablers of ecohealth for a case study on health and environmental sanitation in Hà Nam, Vietnam - Vi Nguyen; Hung Nguyen-Viet; Phuc Pham Duc; Stephen, C.; McEwen, S.A. (Springer, 2014)
Background To date, research has shown an increasing use of the term “ecohealth” in literature, but few researchers have explicitly described how it has been used. We investigated a project on health and environmental sanitation (the conceptual framework of which included the pillars of ecohealth) to identify the impediments and enablers of ecohealth and investigate how it can move from concept to practice. Methods A case study approach was used. The interview questions were centred on the nature of interactions and the sharing of information between stakeholders. Results The analysis identified nine impediments and 15 enablers of ecohealth. Three themes relating to impediments, in particular—integration is not clear, don’t understand, and limited participation—related more directly to the challenges in applying the ecohealth pillars of transdisciplinarity and participation. The themes relating to enablers—awareness and understanding, capacity development, and interactions—facilitated usage of the research results. By extracting information on the environmental, social, economic, and health aspects of environmental sanitation, we found that the issue spanned multiple scales and sectors. Conclusion The challenge of how to integrate these aspects should be considered at the design stage and throughout the research process. We recommend that ecohealth research teams include a self-investigation of their processes in order to facilitate a comparison of moving from concept to practice, which may offer insights into how to evaluate the process.